2017
DOI: 10.5935/2359-4802.20170032
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Cardiovascular Risk Factors, Fitness, and Quality Of Life in Hiv+ Children and Adolescents: Pilot Study

Abstract: Children and adolescents infected by HIV through mother-to-child transmission are at high risk of developing premature cardiovascular diseases due to dyslipidemia, insulin resistance and low-grade chronic inflammation. The aim of the pilot study was to verify the effect of a playful exercise program on cardiovascular, morphological, metabolic, fitness, and quality of life outcomes. A non-randomized clinical trial consisting of 24 sessions of playful aerobic and resistive exercises was applied to 10 children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In addition to that, studies that aimed to investigate the relationship between HIV infection/ART use and the health-related physical fitness components showed changes in the body fat distribution [91,104,194,264], reduction in the bone mass [15,84,108,124,209,262] and fat-free mass [8,102]. However, only 12.2% (n = 30) of the studies investigated more than one the health-related physical fitness component [21][22][23][24][25][26][27][28][29][30][31]33,34,41,47,50,52,106,110,112,116,192,196,[221][222][223]226,230,233,238] and no study that investigated the relationship between the health-related physical fitness components was found. Muscular strength/endurance is directly associated with the amount of muscle fibers-that is, related to the amount of fat-free mass, specifically muscle tissue, as well as cardiorespiratory fitness-is directly associated with the amount of type I (oxidative) muscle fibers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, studies that aimed to investigate the relationship between HIV infection/ART use and the health-related physical fitness components showed changes in the body fat distribution [91,104,194,264], reduction in the bone mass [15,84,108,124,209,262] and fat-free mass [8,102]. However, only 12.2% (n = 30) of the studies investigated more than one the health-related physical fitness component [21][22][23][24][25][26][27][28][29][30][31]33,34,41,47,50,52,106,110,112,116,192,196,[221][222][223]226,230,233,238] and no study that investigated the relationship between the health-related physical fitness components was found. Muscular strength/endurance is directly associated with the amount of muscle fibers-that is, related to the amount of fat-free mass, specifically muscle tissue, as well as cardiorespiratory fitness-is directly associated with the amount of type I (oxidative) muscle fibers …”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have showed that: (I) muscular strength/endurance is directly associated with the number of muscle fibers, where the greater the number of muscle fibers, the greater the muscular strength/endurance values [48,49]; (II) cardiorespiratory fitness is directly associated with the amount of type I (oxidative) muscle fibers, where the greater the number of type I muscle fibers, the greater the cardiorespiratory fitness [48,49]. Thus, focusing mainly on only one specific component limits the understanding of whether the changes observed in the investigated component were explained by changes in another component, or furthermore, whether these changes result in changes in other components as a ripple effect [28,33,[50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has improved cardiovascular function in PLHIV [22][23][24][25]. For example, Orozco and Rosario (2020) found that Hispanic-Latinos living with HIV who participated in a community-based exercise program for one year demonstrated improved CD4 count and heart rate achieved during a submaximal test [16].…”
Section: Introductionmentioning
confidence: 99%
“…A aptidão física tornou-se uma importante condição a ser avaliada em estudos epidemiológicos, visto que, seus valores reduzidos estão diretamente associados à mortalidade precoce (LANG, 2018), e pelo fato de estar diretamente ligada a saúde do indivíduo, da mesma forma vem sendo bastante estudada nos últimos anos na área de educação física (GODOI FILHO;FARIAS, 2015) e áreas a fim (PENHA et al, 2019;REUTER et al, 2019;LIMA et al, 2017).…”
Section: Introductionunclassified